Strategi Bauran Pemasaran Yang Digunakan My Kripick PT Bayou Berjaya Indonesia Untuk Meningkatkan Penjualan - Rizky Ahmad Pribadi; Putri Sri Lestari; Dwi Epty Hidayaty (Journal of Management and Social Sciences, 2023)
Micro, Small, and Medium Enterprises (MSMEs) are an activity that is one of the sources of the country's economic power. The purpose of this observation activity is to determine the 7P marketing mix strategy implemented by PT Bayou Berjaya Indonesia, which started its business in the midst of a pandemic. The pandemic in Indonesia has had many negative impacts on business turnover in Indonesia, especially in the food and beverage sector The research was conducted using descriptive and observative methods by conducting in-depth interviews on the business that is My Kripick. The results of the research (the product becomes a trend maker in the West Java market. (2) Product prices can compete with the market. (3) Offline stores are the main place for increased the turnover. (4) Promotion is carried out through soft selling metode. (5) Manager level consists of two people, chief operational officer and chief marketing officer. (6) Using a ready stock system. (7) Using a unique design product.